THE INVESTIGATION OF THE RELATIONSHIP BETWEEN NARCISSISM, PERFECTIONISM, LONELINESS, DEPRESSION, SUBJECTIVE AND PSYCHOLOGICAL WELL-BEING IN A SAMPLE OF TRANSYLVANIAN HUNGARIAN AND ROMANIAN STUDENTS - ÉVA KÁLLAY (Studia Universitatis Babes-Bolyai, 2020)
ABSTRACT. The last decades have witnessed a significant increase in several forms of human psychological malfunctioning, aspects that proved to significantly endanger healthy and efficient human adaptation. Mental health indicators (anxiety, depression, reduced levels of happiness), perfectionism, narcissism, and loneliness have significantly increased, despite the significant improvement of existent life-conditions. The market-based competition and reward system in the educational and professional spheres, as well as the perfectionistic expectations specific to the personal life impose high demands on the individual, which usually become sources of significant chronic stress, further impacting the individual's quality of life (psychological and subjective well-being, loneliness). The comparative investigation of the above-mentioned variables in Transylvanian Hungarian and Transylvanian Romanian students would offer us the chance to compare these levels of functioning in two, culturally different samples. Our present study is a continuation and refinement of previous studies, and concentrates on the following major aims: (i) the investigation of the possible differences in narcissism, perfectionism, loneliness, depression, happiness, subjective and psychological well-being in Transylvanian Hungarian and Transylvanian Romanian first and second year students; (ii) the investigation of the association patterns between variables in both samples, and (iii) the examination of the role the studied variables play on the major indicators of mental and psychological health (depression and happiness) both in the united sample and on the two samples of students separately. The results of our investigation may be beneficial for the tailoring of future prevention and intervention programs that would target the enhancement of psychological adaptation of Transylvanian students.